Pengaruh Sasaran Kebijakan Ngawi Hijau Terhadap Perilaku Kewirausahaan Hijau Pelaku UMKM Penolahan Kayu di Kabupaten Ngawi - Kartiko, Yuwono (Indra Institute Research & Publication, 2025)
The study focuses on the impact of the Ngawi Green policy on green entrepreneurial behavior in wood processing SMEs in Ngawi. This study uses a quantitative method with a questionnaire as a method of collecting data. The number of respondents in this study was 150 Wood Industry SMEs in Ngawi who have business licenses. This study discusses the important role of small and medium enterprises (SMEs) in the wood processing industry in Ngawi, which employed 20,837 people in 2019 and contributed to regional economic growth of 22% from 2016 to 2019. This is dominated by wood processing SMEs, with 8,647 units, compared to other industries such as food and textiles. In this study there are 2 variables, namely the endogenous variable (Y) Green Entrepreneurial Behavior of SMEs and the exogenous variable (X) Policy Targets. The results of the study indicate that policy targets have a positive and significant influence on the realization of green entrepreneurial behavior in wood industry SMEs in Ngawi.